Bridging the gap between formal and non-formal science education: traditional fish markets as a tool to promote ocean literacy. Issue 3 (3rd July 2022) - Aurélio, Luísa; Sequeira, Vera; França, Susana; Amoroso, Sandra; Boaventura, Diana; Cardoso, Inês; Amorim, Ana; Cabral, Henrique N.
Abstract: Raising awareness on marine environmental issues is crucial to deepen students' knowledge on ocean sustainability. Nonetheless, ocean-related topics have not been adequately addressed through formal education curricula, thus non-formal learning activities were developed to promote Ocean Literacy among students. These include visits to the local fish market and hands-on activities of fish biological sampling. A mixed methodology with closed and open-self questionnaires and interviews, was used to assess the activities' effect in student's learning and to evaluate their implementation and importance. Results showed the activities contribution to the increased learning while promoting a more active citizenship regarding ocean conservancy.